Masocriticism - Mann, Paul, 1948- (SUNY series in postmodern culture., 1999)
These essays on literary theory, philosophy, and cultural criticism describe, in their form and content, the end of criticism, even while performing the endlessness of that endgame. In a sense, the book deconstructs all forms of critique and criticism, including deconstruction, and including its own self. That the book is so painfully aware of the futility of its own enterprise, even while pursuing it relentlessly and with such critical rigor, is what makes this a book of masocriticism as well as about masocriticism. -- Provided by publisher.